Concept of Srotas, Srotodushti, and its Applied Clinical Aspects - Sharma, Shruti; Sharma, Ashok Kumar; Sharma, Kishori Lal; Meena, Rekhraj; Goury, Iqbal Khan (International Research Journal of Ayurveda & Yoga, 2023)
The Triguna, Tridosh, Saptadhatu, Oja, Agni, and Srotas are the foundation of Ayurveda’s holistic biology. The body’s internal transportation system, or Srotas, serves as a platform for the actions of other significant bio-factors, such as the three Doshas, the seven Dhatus, the Oja, and the Agni. In the Ayurvedic classics in addition to the circulatory system, the term “Srotas” is used to describe the dynamic interior transport system of the body-mind-spirit organization. According to Ayurvedic Acharyas, an unhealthy lifestyle and unwholesome diet can cause the Srotas system to lose its integrity, which affects the entire range of life processes in both health and sickness. According to Acharya Charak, “Without the help of the Srotas that transport the Dhatus, which are continually undergoing (metabolic) transformations, no structure in the body can grow and develop or waste away and atrophy. To comprehend Ayurvedic biology and medicine, it is necessary to learn both the theoretical and practical aspects of Srotas as without srotodusti (histopathology) no disease can occur.